Diode laser vs. Monopolar electrosurgery in soft tissue crown lengthening and attached gingiva remodeling: assessment of growth factors levels associated with wound healing - Kamel, Asem Mohammed; Ali, Abdullah Ibrahim; Badr, Bahaa Mohammed; Hudu , Shuaibu Abdullahi; Ibrahim, Ibrahim Hammad (Brazilian Dental Science, 2025)
Objective: Diode Lasers and electrosurgery have been widely used as an alternative to scalpel manoeuvre. The implementation of both technology in periodontics was proposed to provide effective, comfortable framework. Thus, the purpose of the current trial was to evaluate healing process after treatment with electrocautery and laser from point of view of growth factors evaluation after soft tissue crown lengthening. Material and Methods: This study was carried out on eighty patients with short clinical crown and tissue of gingiva of anterior segment excised and attached gingiva remodelling done by Diode Laser in group І while in group II done by Electrosurgery. Width and thickness of attached gingiva prior to surgery (baseline), 30 - and 60- days and full mouth bleeding scores and epithelialization were recorded on 7-, 14- and 21 days after operations. Transforming Growth Factor-β1 (TGF-β1), Platelet-Derived Growth Factor-BB (PDGF-BB) and Basic Fibroblast Growth Factor (BFGF) were evaluated. Results: The intergroup comparisons showed statistical significance difference p<0.001 which indicated more effects of Electrosurgery than Diode laser in dispense of width of attached gingiva. Epithelialization was not completed until 21 days of healing in both groups. After 60 days, TGF-β1 and PDGF-BB appeared with no statistical significance difference p= 0.53 in comparison of (DLS) group versus (ES) group while BFGF showed statistical significance difference in comparing (DLS) group versus (ES) group. Conclusion: Diode Laser and Electrosurgery were considered effective for gingivectomy. Electrosurgery was more effective in remodelling gingival width and Diode Laser had more repercussion in bFGF. KEYWORDS Crown lengthening; Diode laser; Electrosurgery; Platelet-derived growth factor; Transforming growth factor beta1.